Characterizing Multi-Walled Carbon Nanotube Synthesis for Field Emission Applications - Crossley, Benjamin L.; Glauvitz, Nathan E.; Quinton, Betty T.; Coutu, Ronald A.; Jr.; Collins, Peter J. (IntechOpen, 2011)
None